Defect handling mechanisms in various open source projects - Awang Abu Bakar, Normi Sham (2011)
Open source projects mostly depend on user feedback to help improve the quality of the developed systems. Similar to other software products, the quality of open source products is related to the number of defects. Products with fewer defects are generally considered to possess higher quality than those with more. In the open source context, defects are located and fixed with the contribution of a large community. The common belief is that open source product quality benefits from this “many eye balls” aspect accompanied with extensive field testing. A survey was conducted to understand defect handling mechanism in selected open source projects and compared the particular approaches taken in different projects. The respondents consisted of the individuals who contributed to 20 medium and large open source projects. The aim of this work is to investigate how the open source developers handle defects with regard to recording, tracking, and resolving these defects. The findings show that consistency of defect recording, completeness of defect records, or even the concept of defect can vary from project to project.